Automated Synthesis of 18F-Fluoropropoxytryptophan for Amino Acid Transporter System Imaging. (20th July 2014) - Shih, I-Hong; Duan, Xu-Dong; Kong, Fan-Lin; Williams, Michael D.; Yang, Kevin; Zhang, Yin-Han; Yang, David J.
Abstract : Objective . This study was to develop a cGMP grade of [ 18 F]fluoropropoxytryptophan ( 18 F-FTP) to assess tryptophan transporters using an automated synthesizer. Methods . Tosylpropoxytryptophan (Ts-TP) was reacted with K 18 F/kryptofix complex. After column purification, solvent evaporation, and hydrolysis, the identity and purity of the product were validated by radio-TLC (1M-ammonium acetate : methanol = 4 : 1) and HPLC (C-18 column, methanol : water = 7 : 3) analyses. In vitro cellular uptake of 18 F-FTP and 18 F-FDG was performed in human prostate cancer cells. PET imaging studies were performed with 18 F-FTP and 18 F-FDG in prostate and small cell lung tumor-bearing mice (3.7 MBq/mouse, iv). Results . Radio-TLC and HPLC analyses of 18 F-FTP showed that the Rf and Rt values were 0.9 and 9 min, respectively. Radiochemical purity was >99%. The radiochemical yield was 37.7% (EOS 90 min, decay corrected). Cellular uptake of 18 F-FTP and 18 F-FDG showed enhanced uptake as a function of incubation time. PET imaging studies showed that 18 F-FTP had less tumor uptake than 18 F-FDG in prostate cancer model. However, 18 F-FTP had more uptake than 18 F-FDG in small cell lung cancer model. Conclusion . 18 F-FTP could be synthesized with high radiochemical yield. Assessment of upregulated transporters activity by 18 F-FTP may provide potential applications in differential diagnosis and prediction of early treatment response.